2023
DOI: 10.1021/acsami.3c02508
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Carbon-Neutral Ammonia Generation via a Cyclic Microwave Plasma Process

Abstract: A novel reactor methodology was developed for chemical looping ammonia synthesis processes using microwave plasma for pre-activation of the stable dinitrogen molecule before reaching the catalyst surface. Microwave plasma-enhanced reactions benefit from higher production of activated species, modularity, quick startup, and lower voltage input than competing plasma-catalysis technologies. Simple, economical, and environmentally benign metallic iron catalysts were used in a cyclical atmospheric pressure synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 45 publications
(90 reference statements)
1
20
0
Order By: Relevance
“…46 Therefore, there are also some redox cycling processes for ammonia production similar to CLAS including electrolytic-chemical cycle, 48,49 as well as some external field-assisted chemical loops for ammonia production, such as plasma-assisted CLAS. 20,50,51…”
Section: Overview Of the Clas Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…46 Therefore, there are also some redox cycling processes for ammonia production similar to CLAS including electrolytic-chemical cycle, 48,49 as well as some external field-assisted chemical loops for ammonia production, such as plasma-assisted CLAS. 20,50,51…”
Section: Overview Of the Clas Processesmentioning
confidence: 99%
“…The results revealed that the K diff and K r increase with the increase of temperature and the potential rate-determining step of the reduction process is the surface reaction. 50 Achieving the reasonable match between the surface reaction rate and the bulk diffusion ability of redox catalysts is an essential approach to improve the reaction performance of redox catalysts in chemical looping processes. It is found by Xiao and co-workers that the introduction of an appropriate amount of Ni can achieve the optimal kinetic matching between surface reaction and bulk diffusion of lattice nitrogen in Mn-based redox catalysts, which ultimately improves the selectivity and yield of Ni–Mn–N composite in the hydrogenation step of CLAS.…”
Section: Rational Design Of Redox Catalysts For Clasmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing efforts have been devoted to improving the efficiency of CLAS process, using the electric or photon energy, ,, structure modulation of NC, ,,,, and kinetics enhancement by adding catalyst. , Similarly, the strong cooperative reactivity of the composite Mn based nitrogen carrier (Mn 4 N and LiH or BaH 2 Mn nitride), could result in the exceptional catalytic activities for ammonia synthesis under mild conditions as compared to that of their parent elements by catalyzing the N 2 fixation and hydrogenation reactions. ,, Suggesting new chemical looping reaction pathways could be another strategy of improving the CLAS process, ,,,, where the easy alloying characteristics of lithium and group 14 elements (Li x M) could provide some interesting results in N 2 fixation through the generation of ternary nitrides. …”
Section: Enroute To the Zero-carbon Artificial Ammonia Synthesismentioning
confidence: 99%